Strategi Penari Rampak Buto Gedruk Desa Jetis Kecamatan Loano Kabupaten Purworejo Dalam Menjaga Konsistensi Gerak Tari - Handarti, Oktavia Silvi Grandis; Eny Kusumastuti (Dinasti Research, 2025)
Rampak Buto Gedruk dance stands out as a prominent traditional art form in Jetis Village, Loano District, Purworejo, characterized by its powerful, energetic movements that demand exceptional physical stamina. Maintaining consistency in movement among dancers is paramount for preserving the aesthetic appeal and visual impact of each performance, which includes ensuring rhythmic uniformity, technical precision, and stable formations. However, achieving this consistency presents several challenges, notably physical fatigue and disruptions in concentration. This study aimed to thoroughly describe the specific strategies employed by Rampak Buto Gedruk dancers, particularly within the Langen Turonggo Sari Arts Community, to uphold dance movement consistency and effectively address the difficulties they encounter. Utilizing a descriptive qualitative research method, data were meticulously gathered through direct observation, comprehensive interviews with the community head, trainers, and dancers, alongside careful documentation conducted within Jetis Village. The findings reveal that the primary strategies adopted encompass routine and structured practice sessions designed to strengthen muscle memory; a detailed evaluation of movements through video recordings and personalized feedback from trainers as well as fellow dancers; a strong emphasis on maintaining optimal physical and mental well-being; and cultivating the ability to adapt seamlessly to diverse stage conditions and the inherent pressures of live performance. Collectively, these strategic approaches empower the dancers to navigate both technical and non-technical obstacles, thereby ensuring the continuous preservation and the highest quality presentation of Rampak Buto Gedruk danceas an invaluable cultural heritage of Jetis Village.